Christianity and human rights : an introduction - Witte, John, 1959-; Alexander, Frank S., 1952- (Cambridge, U.K. ; New York : Cambridge University Press, 2010)
"Combining Jewish, Greek, and Roman teachings with the radical new teachings of Christ and St. Paul, Christianity helped to cultivate the cardinal ideas of dignity, equality, liberty and democracy that ground the modern human rights paradigm. Christianity also helped shape the law of public, private, penal, and procedural rights that anchor modern legal systems in the West and beyond. This collection of essays explores these Christian contributions to human rights through the perspectives of jurisprudence, theology, philosophy and history, and Christian contributions to the special rights claims of women, children, nature and the environment. The authors also address the church's own problems and failings with maintaining human rights ideals. With contributions from leading scholars, including a foreword by Archbishop Desmond Tutu, this book provides an authoritative treatment of how Christianity shaped human rights in the past, and how Christianity and human rights continue to challenge each other in modern times"--Provided by publisher.
The Judaic foundations of rights / David Novak -- Ius in Roman law / Charles Donahue -- Human rights and early Christianity / David Aune -- Human rights in the canon law / R.H. Helmholz -- The modern Catholic church and human rights : the impact of the second Vatican Council / J. Bryan Hehir -- Rights and liberties in early modern Protestantism : the example of Calvinism / John Witte, Jr. -- Modern Protestant developments in human rights / Nicholas P. Wolterstorff -- The issue of human rights in Byzantium and the Orthodox Christian tradition / John A. McGuckin -- The human rights system / T. Jeremy Gunn -- The image of God : rights, reason, and order / Jeremy Waldron -- Religion and equality / Kent Greenawalt -- Proselytism and human rights / Silvio Ferrari -- Religious liberty, church autonomy, and the structure of freedom / Richard W. Garnett -- Christianity and the rights of children : an integrative view / Don Browning -- Christianity and the rights of women / M. Christian Green -- Christianity, human rights, and a theology that touches the ground / Robert A. Seiple -- A right to clean water / John Copeland Nagle -- The final word : can Christianity contribute to a global civil religion? / Robert N. Bellah.
Includes bibliographical references and index.
Keywords: Human rights -- Religious aspects -- Christianity; Christianity -- Influence; Human rights -- History; RELIGION -- Ethics; Christianity -- Influence; Human rights; Human rights -- Religious aspects -- Christianity; Christentum; Menschenrecht; Christentum; Menschenrecht; Kristendom; Religion och juridik; x; Christianity - Influence; Human Rights - History; Human Rights - Religious Aspects - Christianity; History